MATLAB/Simulink Medical CO2 insufflator model with PID - MERAD HADIL; Leila Amal Vilbois (AMAR TELIDJI UNIVERSITY OF LAGHOUAT-FACULTY OF TECHNOLOGY- DEPARTMENT OF ELECTRONIC, 2025)
Our goal is to develop a simulation model of a CO₂ insufflator, a medical device used in laparoscopic (minimally invasive) surgeries to inflate the abdominal cavity with carbon dioxide (CO₂) gas. This creates a working space for surgeons by maintaining a stable intra-abdominal pressure (IAP). using the PID controller with the automatic-tuning optimization tools to ensure fast response, stability, and minimal overshoot.
Instrumentation